Comparison of Self-Concept in Type 2 Diabetes Mellitus Patients between Men and Women at Diabetes Dharma Clinic Perumnas Helvetia Medan in 2019 - Yulis Hati; Rosanti Muchsin; Chatri Julianda Putri (Science Midwifery, 2020)
Self-concept is a person's view of himself. Diabetes mellitus is a chronic disease that can interfere with a person's self-concept because diabetes mellitus sufferers often complain of boredom having to take medication every day, it is difficult to follow the recommended diet, patients have difficulty sleeping because they are always reminded of their illness. Self-concept in men and women who suffer from diabetes mellitus shows a real difference. In living their lives, women are less healthy than men. This study aims to determine the differences in self-concept in people with type 2 diabetes mellitus between men and women. This study uses a comparative description design. The research sample was 38 patients with type 2 diabetes mellitus at the Diabetes Clinic Dharma Perumnas Helvetia Medan in 2019 consisting of 19 men and 19 women. The sampling technique is using purposive sampling technique. Data analysis was performed using the Mann Whitney U test. Based on the results of data analysis, a significance value of 0.001 (p <0.05) was obtained so that the research hypothesis was accepted. This shows that there are differences in self-concept in people with type 2 diabetes mellitus between men and women. The conclusion of this study is that there are differences in self-concept in people with Type 2 Diabetes Mellitus between men and women at the Diabetes Clinic Dharma Perumnas Helvetia Medan. Clinic employees are expected to be able to make nursing plans that can improve self-concept according to the gender of the diabetes mellitus patient.